Online financial disclosures in the Nigerian public sector - Edosa Joshua ARONMWAN; Osariemen ASIRIUWA (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The objective of this study is to examine the online financial disclosure practices by Nigerian public sector entities. In achieving this, the cross-sectional research design was employed and data gathered from 27 states for a one year period. The ordered logistic regression technique was used to estimate the model and the findings reveal that wealth and political competition have significant positive relationships with online financial disclosure in Nigeria while the size of the state has a significant but negative relationship. Also, the age of the state has an insignificant relationship with online financial disclosure in Nigeria. Based on these, the study recommends that healthy competition should be encouraged in forms of public debates, assessment polls on public sector entities, frequent programmes aimed at assessing the progress of public entities probably on a yearly basis or biannual or even at the end of a regime (before the commencement of another)